Pelatihan Desain E-Mabar Interaktif Menggunakan Book Creator Untuk Meningkatkan Algebraic Thinking Pada Mgmp Matematika Smp Di Muaro Jambi - Winarni, Sri; Kumalasari, Ade; Marlina, Marlina; Junita, Ranisa; Rohati, Rohati (Fakultas Sains dan Teknologi, Universitas Jambi, 2024)
Algebra is basically a problem-solving tool and the beginning of a journey that provides skills to solve more complex problems. In solving algebra problems it isnot enough to be proficient in counting, students must adapt the use ofsymbols/variables in their operations. This adjustment involves algebraic thinking.Algebraic thinking is an activity of generalizing mathematical problem patterns thatsupports three components, namely factual, contextual, and symbolicgeneralization. Teachers must be skilled in using learning media to support students'algebraic thinking process to run optimally in the learning process. One practicalmedium to use is an e-module. However, conventional e-modules tend to only displayvisuals in the form of static images. To be able to create interactive e-modules thatare able to combine audio, visual, and ICT components, a supporting platform isneeded. One platform that can be used is Book Creator. Book Creator is equippedwith features for designing and inserting various forms of learning material, suchas documents, power points, videos, images, and audio. The aim of this service is totrain teachers in designing interactive e-Mabar (algebra e-modules) using BookCreator to improve algebraic Thinking. The method used is descriptive qualitative.Data collection techniques used were observation, questionnaires, documentation,and interviews. The results obtained by the Muaro Jambi Regency Middle SchoolMathematics MGMP teachers gained new insights regarding learning mediamakers in designing modules and they were very interested in implementing them inlearning